2010
DOI: 10.1002/eji.200939638
|View full text |Cite
|
Sign up to set email alerts
|

The effect of placental malaria infection on cord blood and maternal immunoregulatory responses at birth

Abstract: Placental malaria (PM), a frequent infection of pregnancy, provides an ideal opportunity to investigate the impact on immune development of exposure of the foetal immune system to foreign Ag. We investigated the effect of PM on the regulatory phenotype and function of cord blood cells from healthy Gambian newborns and peripheral blood cells from their mothers, and analyzed for effects on the balance between regulatory and effector responses. Using the gold standard for classifying PM we further distinguished b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
60
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 45 publications
5
60
1
1
Order By: Relevance
“…+ FOXP3 + cells only after in vitro stimulation with merozoites or staphylococcal enterotoxin B in offspring of women with chronic or past but not active malaria (37). A third study found no association with placental malaria and T regs in cord blood (38), similar to the lack of association with malaria infection in women for the current study.…”
Section: Cd25supporting
confidence: 72%
See 2 more Smart Citations
“…+ FOXP3 + cells only after in vitro stimulation with merozoites or staphylococcal enterotoxin B in offspring of women with chronic or past but not active malaria (37). A third study found no association with placental malaria and T regs in cord blood (38), similar to the lack of association with malaria infection in women for the current study.…”
Section: Cd25supporting
confidence: 72%
“…Alternatively, in utero exposure to malaria blood-stage Ags may trigger activation and expansion of regulatory T cells (T regs ) and/or increased production of immunomodulatory cytokines such as IL-10 or TGF-b (33)(34)(35). Recently, several studies have identified expanded populations of CD4 + T cells capable of producing IL-10 in cord blood from offspring of women with placental malaria when compared with those without placental malaria (36,37). In some of these studies, specifically CD4 + CD25 hi cells have been shown to be an important source of 38 (37).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, a deregulation of cytokine networks can lead to adverse pregnancy outcomes including spontaneous abortion, preterm labour, pre-eclampsia, and intrauterine growth restriction [76,77]. Such is the case of gestational malaria, in which a pro-inflammatory status has been confirmed and contributes to explain the deleterious effect of P. falciparum infection in mother and fetus [78].…”
Section: Regulation Of the Immune System During Pregnancymentioning
confidence: 99%
“…Placental malaria was assessed in maternal placental biopsies by microscopy (50). Further venous blood samples of 1 ml/kg (maximum 5 ml) were collected at 4 1/2 and 9 mo of age and a TB questionnaire was completed to assess for TB exposure.…”
Section: Blood Sampling and Follow-upmentioning
confidence: 99%